Jean Painlevé et le cinéma animalier - Frédérique Calcagno-Tristant (Communication)
In this article, the work of filmmaker/researcher, and precursor to the scientific vulgarization film, Jean Painlevé, is a pretext to understanding the mouvance of genres. Here, we will see emerge, each time in a particular socio-historical context, the process of hybridization and further, will show the discrete even dissimulated dimension. In order to do this, we will operate according to pluridisciplinary methods linked to the semiotics of the image, the semiotics of cinema, narratology, and aesthetics considered in its aesthetic form.